Pengaruh Corporate Social Responsibility, Capital Intensity dan Inventory Intensity terhadap Penghindaran Pajak - Amendy, Diantia; Afandi, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to analyze the effect of corporate social responsibility, capital intensity and inventory intensity on tax avoidance on coal mining subsector companies listed on the Indonesia Stock Exchange in the period 2016-2018. This type of research is quantitative. The population of this research is the coal mining subsector company listed on the Indonesia Stock Exchange in the period of 2016-2018 consisting of 27 companies. The research sample consisted of 8 companies. The sampling technique in this study used purposive sampling. The data used in the form of an annual report on coal mining subsector companies listed on the Indonesia Stock Exchange. Testing the hypothesis in this study using the method of multiple linear regression analysis with the SPSS program. The results showed that inventory intensity affects tax avoidance. While corporate social responsibility and capital intensity do not affect tax avoidance.